Kepuasan pemustaka Perpustakaan UIN Sunan Gunung Djati Bandung dan pengaruh word of mouth pemustaka - Nailah Hanum Hanany; Eded Sudirman (Universitas Padjadjaran, 2019)
Library activities that are directly felt by users are services, which are considered the spearhead of libraries. Guarantee and empathy aspects of the Servqual Model and effect of service aspects on the LibQual + TM model are all closely related to one of the factors, namely librarian language skills, both verbal and non-verbal. Moreover, users who have used these services can be effective promotional tools to affect other users through Word of Mouth (WOM) promotion. WOM in an Islamic perspective can mean ‘da'wah’, an invitation to do good. This study aimed to examine perceptions of satisfaction with the librarian language skills and their relationship with WOM among UIN Sunan Gunung Djati Library users. Librarian language skills are divided into two categories, namely verbal and non-verbal. Verbal aspects consist of vocal parameters, word selection, sentence structure, and convenience aspects to be understood. Non-verbal aspects include gesture parameters, body position, tone, and intonation. The research method used survey method with a total sample of 400 users. Determination of the number of samples was performed by Slovin method and selected by accidental sampling technique. Results showed, Consumer Satisfaction Index (CSI) for verbal communication was 3.325, and non-verbal communication was 3.253. Both were in the